Study of quality of water wells in Iguape-CE - Miguel Paulo Rodrigues Neto (2014)
According to the United Nations (UN), the target of one of the objectives Development Goals of halving the number of people without access to water drinking was reached - however, 768 million people still do not enjoy this advance overall, especially in rural areas. In this context, the population of Iguape, a district of municipality of Aquiraz-EC, is part of this minority, lacking sewage and supply for water distribution network. Thus, a study was performed to During the year 2013 with the objective of determining if the water wells used by population - the main source of those goods - was in accordance with the parameters of potability provided for in the regulations. The results show that for the plurality of wells human consumption have parameters outside the limits accepted by the existing laws - presence of E. coli, for example. As a reference for this study the Quality Index Canadian Council of Ministers of the Environment was employed to facilitate the Understanding of the data set and revealed that the ten wells monitored only one presents water quality rated as Good.